Chronic Inflammatory Demyelinating Polyradiculoneuropathy in Association With Concomitant Diseases: Identification and Management - Chen, Yan; Tang, Xiangqi (Frontiers in Immunology, 2022)
Chronic inflammatory demyelinating polyradiculoneuropathy (CIDP) is a rare, heterogeneous, but treatable autoimmune-mediated peripheral neuropathy characterized by demyelination. CIDP can occur independently or simultaneously with a variety of diseases such as diabetes, monoclonal gammopathy of undetermined significance (MGUS), connective tissue disease, chronic active hepatitis, etc. It is important to identify CIDP and specific peripheral neuropathies caused by these diseases, this review aims to summarize the CIDP literatures related to diabetes, MGUS and SLE, and hope to be helpful for the management for such patients.